Wave Diffraction and Independent Radiation by a Buoyant Body in Finite-Depth Water by Using an Exact NtD Boundary Condition - Un-Ryong Rim; Hyo-Song Ko; Gum-Chon Ri (International Journal of Marine Engineering Innovation and Research, 2025)
Hydrodynamics of a floating structure is of interest from offshore and coastal engineers who develop the wave energy converters and utilize the marine space resources. Recently, Rim [1-3] proposed an exact DtN (Dirichlet-to-Neumann) artificial boundary condition in order to solve three dimensional wave-structure interactions or wave motion over piecewise topographies numerically. This paper is concerned with another artificial boundary condition or so-called NtD (Neumann-to Dirichlet) boundary condition in order to solve water wave diffraction and independent radiation by a buoyant body. A virtual cylindrical surface enclosing the floating body is chosen as a boundary on which an exact NtD map is analytically derived from a solution of the exterior subregion and then it is specified as a boundary condition in order to solve the interior problem. The present model shows good accuracy through the comparison with the DtN approach and suggests the escalated results for the effects of heading angle of incident wave and draft of a buoyant chamfer box.